2011
DOI: 10.1021/ja209165r
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of H Cluster Oxidation

Abstract: The H2-evolving potential of [FeFe] hydrogenases is severely limited by the oxygen sensitivity of this class of enzymes. Recent experimental studies on hydrogenase from C. reinhardtii point to O2-induced structural changes in the [Fe4S4] subsite of the H cluster. Here, we investigate the mechanistic basis of this observation by means of density functional theory. Unexpectedly, we find that the isolated H cluster shows a pathological catalytic activity for the formation of reactive oxygen species such as O2– an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 87 publications
10
74
0
Order By: Relevance
“…The results suggested that O 2 induces degradation first of the cubane cluster while leaving the diiron unit largely intact [41][42]. A similar mechanism has been supported by DFT calculations [43]. A similar mechanism has been supported by DFT calculations [43].…”
Section: [Fefe]-hydrogenasessupporting
confidence: 57%
“…The results suggested that O 2 induces degradation first of the cubane cluster while leaving the diiron unit largely intact [41][42]. A similar mechanism has been supported by DFT calculations [43]. A similar mechanism has been supported by DFT calculations [43].…”
Section: [Fefe]-hydrogenasessupporting
confidence: 57%
“…Bonds that were cut, when the model was extracted from the crystal structure, were saturated with hydrogen atoms. Their bond lengths were adjusted to the same length as in ref 24, and both atoms of the bond were kept fixed during structure optimization to preserve the structural constraints of the protein matrix (fixed atoms are indicated in Figure 1). Calculations were carried out with version 6.3.1 of the Turbomole program package.…”
Section: Computational Methodologymentioning
confidence: 99%
“…According to X-ray absorption measurements, exposing the enzyme from Cr to O 2 damages the 4Fe4S subcluster; this suggested that O 2 binding to Fe d results in the formation of a reactive oxygen species (ROS) that diffuses towards the 4Fe4S subcluster and destroys it. 16,18 According to the DFT studies of Reiher 19,20 and Pachter, 21 this ROS could be the OOH radical or H 2 O 2 . However, this mechanism conflicts with a recent report according to which the O 2 -damaged enzyme from Cr harbors an intact 4Fe4S subsite and no 2Fe subcluster, and the observation that the O 2 -damaged enzyme is repaired upon insertion of a synthetic analogue of the 2Fe subcluster.…”
Section: Introductionmentioning
confidence: 99%